Diagnostic Approach of Lung Cancer: A Literature Review - Jesi Hana; Novia Nurul Faizah (Faculty of Medicine Universitas Airlangga, 2023)
Lung cancer is the second most commonly diagnosed malignancy with the highest mortality rate. It can be classified into small-cell lung carcinoma (SCLC) and non-small-cell lung carcinoma (NSCLC). At the early stage of the disease, lung cancer rarely gives apparent symptoms. Patients are usually diagnosed at an advanced stage. Lung cancer is closely related to tobacco smoking. The increasing prevalence of tobacco smoking in Indonesia should be an alarm. During the last decades, knowledge and technology regarding lung cancer screening and diagnosis have vastly increased. Proper screening for high-risk individuals will help to increase the survival rate from the disease. Diagnosis of lung cancer using various radiologic modalities, histopathology, and biomolecular tests will also determine a specific treatment approach for the patient. A proper diagnostic test will also help predict the patient's prognosis. This literature review aimed to provide foundation knowledge from recent guidelines for screening and diagnosing lung cancer.